2000
DOI: 10.1002/1097-0134(20000901)40:4<637::aid-prot80>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Polymer principles of protein calorimetric two‐state cooperativity

Abstract: The experimental calorimetric two-state criterion requires the van't Hoff enthalpy DeltaH(vH) around the folding/unfolding transition midpoint to be equal or very close to the calorimetric enthalpy DeltaH(cal) of the entire transition. We use an analytical model with experimental parameters from chymotrypsin inhibitor 2 to elucidate the relationship among several different van't Hoff enthalpies used in calorimetric analyses. Under reasonable assumptions, the implications of these DeltaH(vH)'s being approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
135
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(144 citation statements)
references
References 82 publications
7
135
1
1
Order By: Relevance
“…This condition implies a two-state-like enthalpy distribution at the transition midpoint, with a high free-energy barrier separating the folded and unfolded states of a given protein. 49 Recent analyses 56,62 showed that the ΔH vH /ΔH cal ≈ 1 condition is intimately related to a high Z score (commonly used in protein structure prediction) as well as a large T f /T g ratio between folding and glass-transition temperatures in energy landscape theories (see Eqs. (5) and (6) on pp.…”
Section: Criteria For Folding Cooperativitymentioning
confidence: 99%
See 2 more Smart Citations
“…This condition implies a two-state-like enthalpy distribution at the transition midpoint, with a high free-energy barrier separating the folded and unfolded states of a given protein. 49 Recent analyses 56,62 showed that the ΔH vH /ΔH cal ≈ 1 condition is intimately related to a high Z score (commonly used in protein structure prediction) as well as a large T f /T g ratio between folding and glass-transition temperatures in energy landscape theories (see Eqs. (5) and (6) on pp.…”
Section: Criteria For Folding Cooperativitymentioning
confidence: 99%
“…The high degree of cooperativity of many barrier-limited proteins is a physically remarkable property, 49 suggesting that cooperativity itself is a consequence of stringent biological selection. [50][51][52] This recent finding from theory 49,53,54 and experiment 50 poses a serious conceptual challenge since natural two-state proteins are significantly more cooperative than coarse-grained protein chain models 55 constructed to embody common intuitive notions of pairwise additive interactions 56 (e.g., the hydrophobic-polar interaction scheme 57,58 ). Apparently, only models that explicitly 59,60 or tacitly 61 (see comment on pp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 It was soon realized 38,39 that a likely origin for this shortcoming is that continuum Gō-like models with pairwise-additive Lennard-Jones-like potentials as well as common lattice Gō models fold less cooperatively than real two-state-like proteins. 40,41 Lattice modeling efforts inspired by this realization showed more diverse folding rates when cooperativity was enhanced by nonadditive many-body energy terms. 38,39 These studies further suggested that the remarkable diversity of experimental folding rates among two-state-like proteins is probably underpinned by specific, rather than generic, forms of many-body interactions, for there are substantial variations in folding rate diversity when different many-body interaction schemes were applied.…”
Section: Introductionmentioning
confidence: 96%
“…A series of insightful papers by Chan and co-workers have shown that all past lattice models failed to reproduce the linear dependence of the logarithm of the folding and unfolding rate constants on denaturant concentrations (linear Chevron plot) in a meaningful range of folding rates, a typical folding behavior of small apparent two-state proteins. [37][38][39][40][41] In order to reproduce the linear Chevron plot, they found that a near-flat energy landscape for the unfolded state and an additional stabilizing cooperative energy term (many-body interactions) for the native state were required. Interestingly, hidden intermediates like those observed in the native-state HX experiments in real proteins have also emerged from a new four-helix bundle lattice model when many-body interactions for the formation of the helices are added (H. Kaya & H.S.…”
Section: Structural Implications On Kinetic Unfolding Intermediatesmentioning
confidence: 99%